Peran Ilmu Balaghah dalam Mengungkap Keindahan Al-Qur’an (Pusat Riset dan Inovasi Nasional, 2024)
This article explores the role of balaghah in uncovering the linguistic beauty of the Qur’an, particularly in relation to its structural arrangement, semantic depth, and aesthetic qualities. The study adopts a qualitative design based on library research, drawing data from selected Qur’anic verses and scholarly works on balaghah. Data analysis is conducted using a descriptive-analytical method by examining the three core branches of balaghah, namely ma’ani, bayan, and badi’. The analysis shows that ma’ani contributes to highlighting the appropriateness and effectiveness of sentence structures in accordance with context and communicative intent, while bayan reveals deeper layers of meaning through various rhetorical expressions and figurative styles. Meanwhile, badi’ enhances the aesthetic dimension of the Qur’anic text by emphasizing sound harmony, stylistic balance, and semantic refinement. The integration of these three elements demonstrates that Qur’anic language possesses a holistic beauty that is not merely decorative but also functional, strengthening the delivery of divine messages both semantically and aesthetically.